Young-elderly individuals´ use of social media for travel purpose - Susanna Fabricius; Niklas Eriksson (Tourism & Management Studies)
The population is rapidly ageing in many developed countries. However, little research has been conducted to better understand older individuals’ use of the Internet and social media for travel purposes. This qualitative study focuses on identifying young-elderly (aged 60-75) travellers as disinclined, opportunistic and 2.0 users of social media and on exploring possible enablers and barriers to their use. Fourteen individuals were interviewed, and the results suggest a quite clear divide in how actively social media is used by the informants. Seven informants were categorized as disinclined, six as opportunistic and one as a 2.0 user. There also seem to be heterogeneous perceptions of social media for travel purposes - several possible enablers and barriers were found among the informants to consulting online reviews and blogs for travel planning and to sharing travel experiences online.